2017
DOI: 10.2166/wst.2017.363
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of brewery effluent to cultivate Spirulina sp. for nutrients removal and biomass production

Abstract: Due to the low concentration of nitrate and high contents of organics, brewery effluent was not suitable for the cultivation of Spirulina sp. This work changed the nutrient profile of brewery effluent effectively by dilution, addition of nitrate, and anaerobic digestion. The result showed that the optimum dilution rate and NaNO addition for brewery effluent were 20% and 0.5 g/L, respectively. Spirulina sp. grown in pretreated brewery effluent produced 1.562 mg/L biomass and reduced concentrations of nutrients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…At the end of cultivation, concentrations of residual NH 3 -N, TN, TP, and COD were 23.7, 91.2, 2.4, and 217.9 mg L À1 , meeting the requirement of wastewater discharge standard. 45 This result demonstrated that the pretreatment of AD-SM not only generated economic benets by producing more biomass, but also generated environmental benets by promoting nutrients recycling. (Table 2) 3.4.2 Composition of algal biomass.…”
Section: Algae Cultivation In Pretreated Ad-sm With 4-fold Dilutionmentioning
confidence: 87%
“…At the end of cultivation, concentrations of residual NH 3 -N, TN, TP, and COD were 23.7, 91.2, 2.4, and 217.9 mg L À1 , meeting the requirement of wastewater discharge standard. 45 This result demonstrated that the pretreatment of AD-SM not only generated economic benets by producing more biomass, but also generated environmental benets by promoting nutrients recycling. (Table 2) 3.4.2 Composition of algal biomass.…”
Section: Algae Cultivation In Pretreated Ad-sm With 4-fold Dilutionmentioning
confidence: 87%
“…Specific problems caused by the earlier‐mentioned two issues include: (i) carbon deficiency limits the microalgae growth and slowdowns the uptake rates of other nutrients; (ii) suspended solids may not be degraded and assimilated efficiently by microalgae cells, resulting in low removal efficiency of nutrients. Similar problems were observed in the treatment of other sources of wastewater, such as food processing effluent, agricultural wastewater, and raw municipal wastewater, by microalgae culture …”
Section: Introductionmentioning
confidence: 54%
“…Fast urbanization and industrialization produce a large amount of sludge worldwide, particularly in developing countries . One such country is China, where the amount of sludge production reached 1.3 million tons (dry weight) by 2008 and is increasing at an annual rate of 10% .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Considering the harmful effects of alkaline environment on microalgal metabolism, pH value of microalgae film should be controlled around 6.5. 20 Comparison of Fig. 3(c) and (d) showed that in the purification process (20 min), no significant difference was observed in fine particulates removal between rehydrated vacuum-dried microalgae and living microalgae.…”
Section: Test Of Surface Charge Hypothesismentioning
confidence: 88%